2005
DOI: 10.1080/01446190500204705
|View full text |Cite
|
Sign up to set email alerts
|

Improvement tools in the UK construction industry

Abstract: The use of improvement tools in manufacturing industry has proven to be an important aspect of continuous improvement activities. To determine whether the same is true in the UK construction industry, a survey was conducted to assess the current level of use and perceived importance of such tools. In addition, the impact of the ISO 9001 quality system on the level of use and perceived importance of these tools was also investigated. Following a comprehensive literature review, more than thirty improvement tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…According to Denscombe (2003) and Delgado-Hernandez and Aspinwall (2005), questionnaires are most appropriate where responses are required from a large number of geographically disparate respondents. Burns (2000) also believes that questionnaires can improve the reliability of the research study due to their use of standardised responses from all participants, whereas Saunders et al (2009) suggested that the questionnaire approach is "one of the most widely used data collection techniques".…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Denscombe (2003) and Delgado-Hernandez and Aspinwall (2005), questionnaires are most appropriate where responses are required from a large number of geographically disparate respondents. Burns (2000) also believes that questionnaires can improve the reliability of the research study due to their use of standardised responses from all participants, whereas Saunders et al (2009) suggested that the questionnaire approach is "one of the most widely used data collection techniques".…”
Section: Methodsmentioning
confidence: 99%
“…The perspective on sector or market is quite interesting as previous studies on improvement tools and techniques have tended to concentrate their focus on singular/limited sectors or countries. For example, Qui and Tannock (2010) and Esain, Lethbridge, and Elias (2011) focused on China and Wales respectively while Delgado-Hernandez and Aspinwall (2005) focused on the construction industry. Therefore, while studies such as Johnston and Clark (2008), and Fitzsimmons and Fitzsimmons (2011) have suggested that improvement tools and techniques have applicability in both public and private sector organisations, there is a dearth of comparative studies that have studied cross-sector adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach has been suggested by a number of scholars [31,32] especially in the field of e-business tool adoption [33][34][35]. The survey was sent to over 600 managers in over 40 countries and was made available online.…”
Section: Methodsmentioning
confidence: 99%